Locomotion and Topographical Working Memory in Children With Myelomeningocele and Arthrogryposis Multiplex Congenita - Bartonek, Åsa; Guariglia, Cecilia; Piccardi, Laura (Frontiers in Psychiatry, 2021)
ABSTRACT The aim of the present study was to explore topographic working memory in children with myelomeningocele (MMC) and arthrogryposis multiplex congenita (AMC). To this purpose we assessed 41 children with MMC and AMC, assigned an ambulation group, and 120 typical developing (TD) children, mean age 11.9, 10.6 and 9.9 years respectively. All groups performed a topographic working memory test (WalCT) while moving in the walking space and a visuo-spatial working memory test (CBT) in the reaching space. Children with MMC and AMC performed also a test to measure their ability to reason on visuo-spatial material the Raven’s Coloured Progressive Matrices (CPM). Results showed a WalCT span shorter in the MMC group than in the TD group. In general, all ambulation groups had a shorter WalCT span than the TD group. CBT span was shorter in the non-ambulation (Na) group than in the TD group. Even though higher cognitive score was found in the community ambulation group than in the Na group, topographic working memory was affected similarly in both groups. Comprising children who develop community ambulation in therapy program including aspects of navigation may gain even children with low levels of MMC and AMC. These results evidenced the importance of the motor development and navigational experience gained through direct exploration of the environment in topographic memory.